Analisis Self-Confidence Siswa SMA Kelas XI dalam Pembelajaran Matematika - Juliana, Intan Wahyuni; Abadi, Agung Prasetyo (Jurnal Didactical Mathematics, 2025)
Self-confidence is important for learning because it makes individuals more optimistic during the learning process. This study aims to analyze and measure the average ratio of self-confidence levels among students of class XI.B at SMA Negeri 1 Klari in learning mathematics. A qualitative approach was employed, and a case study was conducted on 34 students from class XI.B. The sampling technique used in this research was purposive sampling. The research instrument was a non-test instrument, and the data collection technique involved a questionnaire. The results showed a percentage of 80.07% for the first indicator, 81.39% for the second indicator, 78.00% for the third indicator, and 78.43% for the fourth indicator. These findings indicate that the self-confidence of class XI.B students in learning mathematics is generally at a fairly good level.